(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article suggested ways to develop and increase the efficiency of advertising services in Samarkand region, studied the factors affecting advertising services, evaluated the results of the multifactorial regression equation and developed a forecast for the next three years.